2017
DOI: 10.1111/ecog.03348
|View full text |Cite
|
Sign up to set email alerts
|

The importance of snow in species distribution models of arctic vegetation

Abstract: Snow cover is characteristic of high‐latitude and ‐altitude ecosystems where snowpack properties regulate many ecological patterns and processes. Nevertheless, snow information is only rarely used as a predictor in species distribution models (SDMs). Methodological difficulties have been limiting both the quality and quantity of available snow information in SDMs. Here, we test whether incorporating remotely sensed snow information in baseline SDMs (using five climate‐topography‐soil variables) improves the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 88 publications
(95 reference statements)
3
103
1
Order By: Relevance
“…), our study highlights the underused potential of Landsat imagery in this context (Macander et al. ; Niittynen and Luoto ; Niittynen et al. ).…”
Section: Discussionsupporting
confidence: 53%
“…), our study highlights the underused potential of Landsat imagery in this context (Macander et al. ; Niittynen and Luoto ; Niittynen et al. ).…”
Section: Discussionsupporting
confidence: 53%
“…Arabis caerulea, Salix herbacea). Based on correlations between vegetation plots and environmental variables, the growing degree days and the growing season length appeared to be between the most explicative variables, confirming how snow persistence influences vegetation communities (Braun, 1913;Niittynen and Luoto, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…In northern Norway, especially, the relatively mild climate and humid air from the ocean result in thick winter snow packs that can provide a significant decoupling between air, surface and soil temperature (Pauli et al, ; Thompson et al, ). Such an insulating snow pack can affect plant life in several ways, through its effects on overwintering survival, productivity, reproductive success and nutrient and water availability (Niittynen & Luoto, ), with both positive (e.g., fewer frost events) and negative effects (e.g., limited growing season) observed. For many species in the region, especially low‐growing forbs and graminoids, we have shown that using near‐surface soil temperatures instead of free‐air temperatures, which allows the incorporation of these snow cover effects, is crucial to describe the distribution of small‐stature plants accurately (Niittynen & Luoto, ; Randin, Vuissoz, et al, ).…”
Section: Discussionmentioning
confidence: 99%